An explorative study of the synergy between social enterprises and local micro-entrepreneurs in the provision of off-grid clean energy access - Pailman, Whitney Lisa (Energy Research Centre, 2016)
Alleviating energy poverty requires innovative and sustainable business models for delivering energy access. Social enterprises have entered off-grid clean energy access markets, pioneering innovative energy access business models, many of which involve the participation of local micro-entrepreneurs. This research study explores the synergy between social enterprises and local micro-entrepreneurs, specifically in terms of the business models used to incorporate local micro-entrepreneurs into off-grid clean energy value chains and the stages of the value chain in which the local micro-entrepreneurs participate. It furthermore identifies key enabling enterprise ecosystem conditions. A qualitative research methodology and a multiple case study design was used. The sample consisted of 11 respondents, selected through purposive sampling. A semi-structured interview served as the primary data collection instrument and a thematic within-case and cross-case analysis was carried out. This research study represents a pioneering effort, contributing to a growing body of knowledge on innovative participatory business models for energy access.